Photonic water dynamically responsive to external stimuli - Koki Sano (Nature Portfolio, 2016)
Some types of fish can change color by modifying their intracellular guanine crystal in response to external stimuli. Here, Sano et al. mimic this effect in a dilute aqueous dispersion containing titanate nanosheets, whose interlayer distance is tunable to match the entire visible light spectrum.